Fossil-driven secondary inorganic PM2.5 enhancement in the North China Plain: Evidence from carbon and nitrogen isotopes. (November 2020) - Lim, Saehee; Yang, Xiaoyang; Lee, Meehye; Li, Gang; Gao, Yuanguan; Shang, Xiaona; Zhang, Kai; Czimczik, Claudia I.; Xu, Xiaomei; Bae, Min-Suk; Moon, Kwang-Joo; Jeon, Kwonho
Abstract: Measuring isotopic ratios in aerosol particles is a powerful tool for identifying major sources, particularly in separating fossil from non-fossil sources and investigating aerosol formation processes. We measured the radiocarbon, stable carbon, and stable nitrogen isotopic composition of PM2.5 in Beijing (BJ) and Changdao (CD) in the North China Plain (NCP) from May to mid-June 2016. The mean PM2.5 concentrations were 48.6 ± 28.2 μg m −3 and 71.2 ± 29.0 μg m −3 in BJ and CD, respectively, with a high contribution (∼66%) from secondary inorganic aerosol (SIA; NO3 −, NH4 +, and SO4 2− ). The mean δ 13 C of total carbon (TC) and δ 15 N of total nitrogen (TN) values differed significantly between the two sites (p-value of <0.001): −25.1 ± 0.3‰ in BJ and −24.5 ± 0.4‰ in CD and 10.6 ± 1.8‰ in BJ and 5.0 ± 3.1‰ in CD, respectively. In BJ, the average δ 15 N (NH4 + ) and δ 15 N (NO3 − ) values were 12.9 ± 2.3‰ and 5.2 ± 3.5‰, respectively. The ionic molar ratios and isotopic ratios suggest that NO3 − in BJ was formed through the phase-equilibrium reaction of NH4 NO3 under sufficient NH3 (g) conditions, promoted by fossil-derived NH3 (g) transported with southerly winds. In BJ, fossil fuel sources comprised 52 ± 7% of TC and 45 ± 28% of NH4 + on average, estimated from radiocarbon ( 14 C) analysis and the δ 15 N and isotope mixing model, respectively. These multiple-isotopic composition results emphasize that PM2.5 enhancement is derived from fossil sources, in which vehicle emissions are a key contributor. The impact of the coal source was sporadically noticeable. Under regional influences, the fossil fuel-driven SIA led to the PM2.5 enhancements. Our findings demonstrate that the multiple-isotope approach is highly advantageous to elucidate the key sources and limiting factors of secondary inorganic PM2.5 aerosols. Graphical abstract: Image 1 Highlights: In Beijing, the contribution of fossil-fuel sources to PM2.5 TC was 52 ± 7%. For NH4 +, the contribution of fossil-fuel sources was 45 ± 28%. Vehicle emissions are main fossil sources responsible for PM2.5 enhancement. High PM2.5 was due to collocated NH3 and NOx emissions in North China Plain.